Intellectual Traditions at the Medieval University (2 vol. set) : the Use of Philosophical Psychology in Trinitarian Theology among the Franciscans and Dominicans, 1250-1350. - Friedman, Russell (Studien und Texte zur Geistesgeschichte des Mittelalters., 2012)
This book presents an overview of the later medieval trinitarian theology of the rival Franciscan and Dominican intellectual traditions, and includes detailed studies of thinkers such as Thomas Aquinas, Henry of Ghent, John Duns Scotus, William Ockham, and Gregory of Rimini.